Analisis Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Pakan Ternak Ayam Pedaging di Kabupaten Jombang Jawa Timur - Panjaitan, Hotman; Cahyanto, Herry (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2017)
Livestock activity is one of the sub activities in agriculture, where with the increase of the welfare of the community, the activities in the field of livestock are also increasing as a consequence of the increase of people's income. Meat as one source of protein is needed by the community, while chicken meat is still a prima donna community in meeting the needs of meat because in addition to the relatively cheap price, good taste, also from the aspect of relative health does not contain lots of cholesterol, therefore Animal feed company, is currently racing to market its production. Marketing mix as attribute inherent to a product that is used as consumer appeal, so that marketing mix must be communicated well to consumer through various media of information to influence consumer. The impact for consumer marketing mix information will be a stimulus in making the decision to buy. From the results of the test of the model in this study, using random sampling, structural equation model (SEM) analysis, and software assistance Amos Version 22, in 201 respondents, able to explain the relationship between marketing mix (product, price, promotion and distribution) Purchase of livestock feed, in the area of Jombang regency. In this study, obtained value of Coefficient of Determination (R2) of 0.816, this indicates that, by executing the marketing mix well, it will push upthe decision of livestock feed purchase of 81.6%. Another thing to be gained from is: that the promotion factor of the marketing mix becomes the most dominant factor influence on purchasing decisions, amounting to 44.8%. Keywords: marketing mix, purchase decision